The Student's Guide to VHDL, Peter J. Ashenden, Morgan Kaufmann - De Giusti, Marisa Raquel (2001)
The Student’s Guide to VHDL teaches the fundamental modeling features of VHDL, showing how the features are used for the design of digital systems. It is organized so that it can be read linearly from front to back, as a structured self-learning guide to the language.